Abstract 1122‐000153: Larger Functional Shunts are Associated with Greater Cerebrovascular Disease Burden - Gadallah, Nancy; Torres, Danisette; Ghori, Arifa; Suhan, Laura; Panezai, Spozhmy; Mehta, Siddhart; Fourcand, Farrah; Kirmani, Jawad (Stroke: vascular and interventional neurology, 2021)
Abstract only Introduction : The relationship between embolic stroke and patent foramen ovale (PFO) is well‐established. Our objective was to evaluate the association between high intensity transient signals (HITS) in contrast‐enhanced transcranial doppler ultrasonography (ceTCD), baseline MRI brain small vessel ischemic changes, and rates of acute ischemic stroke in the setting of focal neurological deficits. Methods : Electronic medical records of subjects with acute onset neurological symptoms who had ceTCD and MRI brain were evaluated. Subjects without a reported Spencer grade and/or MRI brain without available DWI and FLAIR sequences were excluded. Acute stroke rates and baseline Fazekas score in low‐grade (Spencer grade 1–2) and high‐grade (Spender grade 3–5) shunts were analyzed using Z score for 2 population proportions and Mann‐Whitney U test, respectively. Social Science Statistics was used for data analysis. Results : From June 2016 to August 2021, of 7,498 consecutive ischemic stroke patients, 132 patients were identified as possible strokes related to PFO and were hospitalized with focal neurological deficit, underwent ceTCD and MRI brain. Acute stroke was confirmed on DWI in 60% of Spencer grade 1 (n = 73), 72.2% of grade 2 (n = 19), 72.7% of grade 3 (n = 29), and 80% of grades 4 and 5 shunts (n = 11). Acute stroke rates between low grade (grades 1–2) and high grade shunts (grades 3–5), did not reach statistical significance (z = ‐0.9181; p = 0.17879). There was no significant difference in periventricular white matter disease (z = 0.85697; p = 0.19489). Fazekas scores assessing deep white matter disease were statistically significant between low‐ and high‐grade shunts (z = 1.92818; p = 0.0268 Conclusions : A trend towards statistical significance was observed in high‐grade shunt association with higher rate of acute stroke. Deep white matter disease burden may be significantly higher in high‐grade shunts. Further prospective studies are needed to corroborate our findings.